P252 Measuring the mediating effects of Mayo score components for tofacitinib on disease-specific quality of life in ulcerative colitis: data from the OCTAVE programme. (25th January 2019) - Dubinsky, M; Bushmakin, A; DiBonaventura, M; Cappelleri, J; Salese, L; Maller, E; Armuzzi, A
Abstract: Background: Composite efficacy endpoints in ulcerative colitis (UC) clinical trials are typically based on the Mayo score (MS), which includes 4 components: stool frequency, rectal bleeding, endoscopic appearance, and physician assessment. Although disease-specific quality of life (QoL) measures like the Inflammatory Bowel Disease Questionnaire (IBDQ) are also frequently included, it is unclear whether treatment effects on QoL are fully explained by MS changes or if there are other unobserved variables in play. The current study explored the interrelationship among treatment, IBDQ scores, and MS components using a mediation modelling framework. Methods: Pooled data at the end (Week 8) of the two double-blind, identically designed induction studies of tofacitinib (OCTAVE Induction 1 and 2, NCT01465763 and NCT01458951) were used. Tofacitinib is an oral, small-molecule Janus kinase inhibitor approved in several countries for the treatment of ulcerative colitis (UC). A mediation model was specified such that the MS components served as the mediators between treatments (active treatment vs. placebo) and IBDQ domain scores (bowel symptoms, systemic symptoms, emotional functioning, and social functioning). Our primary interest was the extent to which treatment affects the IBDQ domains outside of any change in MS components (ie, the direct path). Results: In total, 1079 patients with moderately to severely active UC at baseline were included. Majority of treatment effect on the IBDQ was mediated by MS components. For all IBDQ domains, the indirect path (ie, the pathway from treatment to MS component and then to each IBDQ domain score) was significant (all p < 0.05) and explained 71.6 to 84.7% of the total effect of treatment on IBDQ domains. Yet, for bowel symptom, systemic symptom, and social functioning IBDQ domains, the direct paths (ie, the pathways from treatment directly to each IBDQ domain) were also significant and explained the remaining 21.0 to 28.4% of the total effect of treatment on IBDQ domains (all p < 0.05). The largest direct effects were observed for systemic symptoms (28.4%) and social functioning domains (27.7%). The smallest direct effect of 15.3% (not significant, p = 0.29) was observed for emotional functioning. Conclusions: Our study suggests that the MS, while important in capturing disease activity, does not fully mediate the treatment effects on IBDQ scores. The results indicate that tofacitinib affects certain aspects of disease-specific QoL—bowel symptom, systematic symptom, social functioning—outside of any benefit from improving stool frequency, rectal bleeding, endoscopic assessment, or physician assessment. These results reinforce the value of disease-specific QoL measures such as the IBDQ in capturing the full benefit of UC treatment.